1991
DOI: 10.1146/annurev.so.17.080191.001103
|View full text |Cite
|
Sign up to set email alerts
|

Household History and Sociological Theory

Abstract: This review examines one of the most fundamental issues of family history, the nature of domestic groups in which people lived in the past. The focus is further limited to the evolution of family forms in Europe. Although such models as those originally proposed by Laslett and Hajnal for western family history have been shown to be wanting, they have served an invaluable role in stimulating and guiding family history research. We are now able to begin to grasp the contours of a much more complex western family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 59 publications
0
57
1
2
Order By: Relevance
“…Households are not simply the product of residence rules but are also affected by demography, life course, and political economic factors (Kertzer, 1991). In the field of household behaviour, a systematic wide range research in social science was conducted by Chayanov in Walker et al (2002:170), who observed that peasant households held farms of different sizes with varying levels of surplus production in which each stage in the household life cycle had a different labour-consumer balance.…”
Section: Livelihood Strategies In the Changing Environmentmentioning
confidence: 99%
“…Households are not simply the product of residence rules but are also affected by demography, life course, and political economic factors (Kertzer, 1991). In the field of household behaviour, a systematic wide range research in social science was conducted by Chayanov in Walker et al (2002:170), who observed that peasant households held farms of different sizes with varying levels of surplus production in which each stage in the household life cycle had a different labour-consumer balance.…”
Section: Livelihood Strategies In the Changing Environmentmentioning
confidence: 99%
“…Selon Kertzer (1991) de même que selon Tolnay (1995), les forces de l'économie politique, sous l'influence du mode de production dominant, exercent une pression sur le quotidien des individus qui adoptent ou délaissent certains comportements en matière de reproduction. Certes orientées par les schèmes culturels desquels sont issus les individus, ces décisions et stratégies en matière de reproduction sont de prime abord le produit des conditions matérielles portées par le mode de production dominant.…”
Section: Concepts Théoriquesunclassified
“…Certes orientées par les schèmes culturels desquels sont issus les individus, ces décisions et stratégies en matière de reproduction sont de prime abord le produit des conditions matérielles portées par le mode de production dominant. L'objectif du paradigme d'économie politique n'est néanmoins pas de faire abstraction de la culture en tant que déterminant proche des stratégies familiales, mais d'accorder une importance accrue aux conditions matérielles portées par le mode de production dominant ainsi qu'à la manière dont s'exerce l'influence jusqu'au pouvoir décisionnel et straté-gique s'opérant au sein du noyau familial (Kertzer, 1991). Étudier les déci-sions et les stratégies prises en matière de veuvage et de remariage requiert que l'on s'intéresse à la structure et à l'organisation matérielle du ménage, entre autres, tout en gardant en tête qu'elles sont le résultat de l'évaluation des contraintes et des opportunités auxquelles font face les individus en état de viduité (Hareven, 1994;Uhlenberg et Chew, 1986).…”
Section: Concepts Théoriquesunclassified
“…Actually, life-cycle servants were more numerous in the joint family households of sharecroppers studied by Barbagli and Kertzer than in the nuclear rural families of southern Italy (Barbagli, 1991;Da Mollin, 1990;Kertzer, 1991;Kertzer & Brettell, 1987). Most data from southern Europe contradict the European marriage model and its classical interaction between neolocality (the formation of an independent household upon marriage) and life-cycle service.…”
Section: Articles In This Issuementioning
confidence: 99%